EVALUASI PENERAPAN SISTEM INFORMASI MANAJEMEN RUMAH SAKIT (SIMRS) DI RSUD HAJI MAKASSAR PROVINSI SULAWESI SELATAN DENGAN MENGGUNAKAN METODE HOT-FIT MODEL - Rahmayanti, Rahmayanti; Surahmawati; Muhammad Saleh (Balai Besar Pelatihan Kesehatan (BBPK) Makassar, 2024)
The Haji Makassar Regional General Hospital (RSUD) still faces several obstacles such as unorganized recording, so that the information produced does not meet management needs, and there is still a lack of skills in managing data. Although it has developed a LAN-based SIMRS application in several units, this system often experiences problems and cannot function perfectly, so it often does not run well. This type of research is quantitative research, which uses a cross sectional approach. The results showed that out of 149 respondents, there were 123 (83.1) people who felt the benefits of using SIMRS, and 25 (16.9) people who felt that the use of SIMRS was less useful. Then a chi-square test was carried out which showed the relationship between human (p-value = 0.014), organization (p-value = 0.002), technology (p-value 0.001) with benefits to the operation of SIMRS. Training is required for SIMRS user staff before the system is implemented in hospitals, as well as whenever there is an update to the SIMRS application. And the management of Haji Makassar Hospital should provide support to SIMRS officers in the form of adequate infrastructure and provide motivation such as awards or recognition for contributions from their hard work.